Empowering health professions educators: enhancing curriculum delivery through customized e-tutorial training on fundamental digital tools - Sadiq, Naushaba; Fatima, Syeda Hanaa; Shabnam, Nadia; Rauf, Ayesha (Frontiers in Medicine, 2024)
Introduction In the dynamic landscape of education, the fusion of technology and learning, commonly termed “technology-enhanced learning” (TEL), has emerged as a transformative phenomenon. This study focuses on the imperative integration of TEL in medical education, recognizing the diverse digital literacy levels of adult learners. The exploration introduces the innovative E-Portal training program, designed to empower health professions educators with essential skills for proficiently employing digital tools in instruction. Methodology A dedicated team of medical educationists conducted a thorough investigation into E-curriculum design and delivery, employing the Moodle Learning Management System as the foundation for the E-Portal training program. The training, spanning crucial stages such as course design, content delivery, self-paced teaching, and quality assessment, facilitated participant progression at individual paces, unlocking subsequent steps upon meeting stipulated prerequisites. A pre-training questionnaire gauged participants’ comprehension of distance learning, e-learning, synchronous and asynchronous teaching, and self-directed study. Subsequent focus group discussion post-training generated rich insights into participants’ experiences, reflections, and identified challenges. Results The results illuminate participants’ limited adeptness with e-learning terminology, successful assimilation of components and functionalities, and heightened confidence in online teaching practices. However, discerned challenges during implementation, such as technical hurdles and engagement issues, highlight the multifaceted nature of TEL integration. While the E-Portal training positively impacted preparedness, participant feedback advocates for improvements in assessment tools, technical training provisions, and exploration of alternative Learning Management Systems. Discussion and conclusion Study emphasizes the ongoing need for diverse training methodologies across Learning Management Systems, acknowledging the evolving nature of education and technology. This study underscores the transformative role of a tailored E-Portal training program in seamlessly integrating digital tools into medical education. The comprehensive insights provided contribute to a nuanced understanding of the advantages, obstacles, and potential avenues for enhancement in curriculum delivery through technology-enhanced learning, thereby propelling the field forward.